Enhancements in Hollow Block Technology: Comprehensive Thermal and Mechanical Characterizations - Joseph Dgheim; Kevin Rizk; Yassine Cherif; Emmanuel Antczak; Elias Farah; Nemr El Hajj (Energies)
This research explores the thermal and mechanical properties enhancement in hollow concrete blocks by incorporating recycled expanded polystyrene (EPS) and crumb rubber (CR). Key thermal properties—including average thermal resistance (<semantics><mover accent="true">R¯</mover></semantics>), average thermal conductivity (<semantics><mover accent="true">λ¯</mover></semantics>), and average specific heat (<semantics><mover accent="true">Cp¯</mover></semantics>)—were analyzed, while mechanical properties were evaluated via compressive strength tests. Findings indicate that the addition of EPS and CR significantly improved thermal resistance, with specific heat and compressive strength remaining within acceptable thresholds. The optimal mixture of 35% EPS and 5% rubber by volume led to a remarkable 49.67% increase in thermal resistance compared to standard hollow blocks while still achieving a compressive strength (<semantics><mover accent="true">σ¯</mover></semantics>) around 7 MPa. These results classify the blocks as non-load-bearing, highlighting their potential for energy-efficient construction using sustainable materials. This research advances sustainable building materials by providing practical solutions to improve building performance in Lebanon.